Social Results of Domestic and Foreign Firms: Case Manufacture of Transport Equipment in Russia - Spitsin, Vladislav V.; Mikhalchuk, Aleksandr A.; Spitsina, Lubov Yu.; Tyuleneva, Nataliya A.; Novoseltseva, Darya A. (International Journal of Economics and Financial Issues, 2016)
The article studies the impact of creation of foreign enterprises on social indicators in the developing countries. We compare social results of foreign and joint enterprises (foreign and joint ownership, FJO) and domestic enterprises (Russian ownership, RO) in manufacturing of transport equipment in various regions of Russia. The multivariate statistical analysis is applied to compare the social results. Using the variance analysis, we find that the level of the average salary and growth rates of employment and payroll of FJO enterprises are higher compared to the RO enterprises. At the same time, FJO enterprises are characterized by a lower labor intensity and payroll-output ratio. The clustering into three pairs of factorial indicators of Russian regions is performed separately for RO and FJO enterprises. The clustering displayed statistically significant differences in the social results among the groups of regions. Keywords: Domestic and foreign and joint enterprises, manufacture of transport equipment, employment and payroll,multivariate statistical analysis. JEL Classifications: C100, J210, J310, L620